2009
DOI: 10.1210/jc.2008-1212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Deficiency and Replacement on Endothelial Function in Asymptomatic Subjects

Abstract: This study shows that 25(OH)D deficiency is associated with endothelial dysfunction and increased lipid peroxidation. Replacement of vitamin D has favorable effects on endothelial function. Vitamin D deficiency can be seen as an independent risk factor of atherosclerosis. Hypovitaminosis D-associated endothelial dysfunction may predispose to higher rates of cardiovascular disease in the winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(183 citation statements)
references
References 38 publications
9
168
3
3
Order By: Relevance
“…Low 25(OH)D levels have been found to be associated with endothelial dysfunction, infl ammation, increased vascular stiffness and high coronary artery calcium scores [5]. In addition, 25(OH)D defi ciency aff ects vascular functions by aggravating atherosclerosis, while treatment with 25(OH)D may have protective eff ects on atherosclerosis [6,7]. Low 25(OH)D levels have been found to be associated with early signs of atherosclerosis such as increased carotid intima-media wall thickness [8].…”
Section: -Oh Vitamin D (25(oh)d)mentioning
confidence: 99%
“…Low 25(OH)D levels have been found to be associated with endothelial dysfunction, infl ammation, increased vascular stiffness and high coronary artery calcium scores [5]. In addition, 25(OH)D defi ciency aff ects vascular functions by aggravating atherosclerosis, while treatment with 25(OH)D may have protective eff ects on atherosclerosis [6,7]. Low 25(OH)D levels have been found to be associated with early signs of atherosclerosis such as increased carotid intima-media wall thickness [8].…”
Section: -Oh Vitamin D (25(oh)d)mentioning
confidence: 99%
“…Recent clinical studies have associated low levels of 25-OH VD with hypertension, coronary artery calcification, and cardiovascular diseases such as myocardial infarction, acute stroke, congestive heart failure, and diabetes mellitus [6][7][8][9]. The mechanisms underlying the role of VD in the prevention of cardiovascular disease are not known; however, they may involve diverse physiological actions on the vascular wall, including reduction of smooth muscle cell proliferation, reduction of secretion of the pro-inflammatory cytokines interleukin-6 and tumour necrosis factor-alpha by macrophages, and increased secretion of the anti-inflammatory cytokine interleukin-10, all acting to reduce vascular inflammation [10,11]. Given its relationship with cardiovascular disease, VD insufficiency may be associated with CT.…”
Section: Discussionmentioning
confidence: 99%
“…Postulated mechanisms for these presumed cardiovascular effects include endothelial dysfunction, inflammation, reduced vessel compliance, detrimental effects via bone proteins such as osteoprotegerin, as well as dysregulation of the renin-angiotensin system and arterial wall calcification because of increased parathyroid hormone levels [10,11]. Additionally, VD effectively preserved the structure of elastic fibres and the ratio of elastic fibres to collagen fibres in the artery media [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adipose tissue may have some influence on endothelial function. Tarcin et al (2009) demonstrated that vitamin D replacement increased serum leptin levels accompanied by improving FMD in asymptomatic subjects. In the present study, ELD did not change the increased body weight in OVX rats.…”
Section: Limitations Of This Studymentioning
confidence: 97%